Identifying palliative care needs in a Portuguese liver unit. (14th May 2018) - Carvalho, Joana Rita; Vasconcelos, Mariana; Marques da Costa, Pedro; Marinho, Rui Tato; Fatela, Narcisa; Raimundo, Miguel; Carvalhana, Sofia; Ramalho, Fernando; Cortez‐Pinto, Helena; Velosa, José
Abstract: Background & Aims: Chronic liver disease is a major worldwide cause of morbidity and mortality. Palliative care policies are not clearly established in chronic liver disease. The NECPAL CCOMS‐ICO© (NECesidades PALiativas/Palliative Needs) is a tool to identify palliative care needs, including a section for liver disease. Aim: The aim of this study was to identify palliative care needs in liver patients hospitalised in a tertiary referral Liver Unit. Methods: Single‐centre prospective observational study. One hundred and twenty patients with cirrhosis were included and NECPAL questionnaire was applied to all patients in a 7‐month period. Results: 84.2% of patients were considered as requiring palliative intervention; however, clinicians identified those needs only in 65.8% of the cases and caregivers in 6.7% of the cases; less than 8% of the patients were referred for palliative care consultation. An excessive use of healthcare resources (positive answer to question 3) was strongly associated with a positive need for palliative care (positive NECPAL): OR 7.305, CI 95% 2.54‐20.995, P  < .001). An excessive use of healthcare facilities has a sensitivity of 84.2% and a specificity of 42.1% for prediction of a positive NECPAL result (AUC 0.710, 95% CI 0.570‐0.850, P  = .004). Conclusions: The NECPAL CCOMS‐ICO© represents a feasible and easy‐to‐use tool to identify palliative care needs in patients with chronic liver disease.